Emerging multinationals, international knowledge flows and economic geography: A research agenda - Dirk Dohse; Robert Hassink; Claudia Klaerding (Kiel Institute for the World Economy (IfW), 2012)
One of the most significant changes in the global economy today is the strong increase in outgoing foreign direct investment (OFDI) from emerging economies to industrialised countries. Whereas investment in less developed countries is often motivated by the sourcing of natural resources and cheap labour, knowledge and technology-seeking is an increasingly important motive for emerging multinationals investing in developed economies. The current paper is focussed on the role of emerging multinationals as knowledge-transfer agents and pursues three aims: First, to unravel the distinguishing features of emerging multinationals (as compared to 'traditional' multinationals), secondly, to critically discuss the usefulness of conventional theoretical concepts in explaining this new phenomenon and thirdly, to launch a research agenda for near-future research on emerging multinationals, with a particular focus on the economic geography of international knowledge flows.
Keywords: F21; F23; M16; O33; 330; emerging multinationals; international knowledge flows; economic geography; Multinationales Unternehmen; Aufstrebende Märkte; Direktinvestition; Schwellenländer-seitig; Wissenstransfer; Wirtschaftsgeographie; Industriestaaten; Schwellenländer